DEVELOPMENT OF STEM EXPERIMENT VIDEO FOR SCIENCE LEARNING: A MOVABLE CHANDELIER - Hayatul Qorryati; Arief Muttaqiin (UNIVERSITAS NEGERI MEDAN, 2023)
This research aimed to produce a valid and practical experimental Video Movable Chandelier on Energy Matters in Living Systems (VMC). This experimental video is equipped with STEM elements and several critical thinking questions. The method used in this research is the development of the Plomp model, which consists of three stages, namely preliminary research, prototyping stage, and assessment phase. This research is limited to two stages which up to the stage of prototype formation. The instrument used was a questionnaire in the form of validity sheets and practicality sheets. The video validity test was carried out by three science education lecturers from FMIPA UNP, while the video practicality test was carried out by a science teacher from SMPN 15 Padang. The results of the validity test of the experimental video showed an average Kappa moment (k) value of 0.92 which was included in the very high category, while the results of the practicality test at the one to one evaluation and small group evaluation stages of the experimental video showed an average Kappa Moment value (k) of 0.90 and 0.94 with very high category as well. With the VMC it can help teachers carry out practicums on Energy Material in Living Systems both at school and at home as additional learning media and train students' abilities to think critically.